Suporte à aprendizagem informal no trabalho: um levantamento com os secretários executivos da Universidade Federal do Pará - OLIVEIRA, Priscila Eny Souza (Universidade Federal do Pará, 2018)
The current society scenario requires individuals to be prepared to deal with the multiple challenges that arise daily in the workplace. Thereby, support for informal learning as a variable that seeks to investigate how colleagues and managers encourage or restrict informal learning initiatives at work, becomes an increasingly relevant instrument either in the development of work activities, or in the improvement of the performance of professionals working in the organizations (COELHO JUNIOR; MOURÃO, 2011). Considering the above, the present study analyzes the support to informal learning in the context of work from the perspective of UFPA executive secretariat professionals through the identification of the factors that influence the learning support and the different perceptions about it. The research was carried out in an exploratory and descriptive way, through a survey, with a quantitative approach and application of the Informal Learning at Work Support Scale, constructed and validated by Coelho Junior (2004) and Coelho Junior., Abbad and Todeschini (2005). For data treatment, descriptive, parametric and multivariate statistical techniques were used. Descriptive analysis showed good support for informal learning at work, while inferential analysis revealed that survey participants perceived an organizational contribution to informal learning. The factor analysis revealed three factors, which explained 74.34% of the data variance and were denominated as: Hierarchical Superior (27.97%); Colleagues (24.21%); and Work Unit (22.16%). And cluster analysis resulted in a classification of interviewees into three groups, with different assessments for the support to informal learning. As conclusions of the study, it was verified that the support is not understood in the same way by the individuals, besides presenting weaknesses and deficiencies. Thus, there is a necessity to consolidate the learning support in the analyzed institution.